"We that are young": Youth and Age in King Lear. Issue 1 (May 2017) - Roberts, Rachel
Abstract : This essay argues that reading Lear 's characters within the paradigm of youth and age reveals the shaping power that stages of life have on each character's response to tragic situations. In fact, age provides characters with a framework for rebellious behavior, a way to cope with suffering, and one path to self-knowledge, that vital but elusive quality throughout Lear . Throughout the play, the venerable age of Lear and Gloucester is constantly evoked to display their lack of wisdom or to create greater pathos as they suffer. The younger characters, particularly Edgar and Cordelia, often frame their behavior in response to the expectations, and sufferings, of their elders. Additionally, Lear's own self-knowledge is tied in important ways to his age – it is important for him to realize not just that he is an ordinary man, fallible like any human, but also that he is an old man. These three ways in which age illuminates character – responding to expected behaviors, to suffering, and to self-knowledge – allow for a reading of Lear framed by age. Throughout this reading, youth and age shape how Lear 's characters understand others and themselves